Current clinical indications for magnetic resonance imaging of the breast. Issue 1 (26th May 2014) - Knuttel, Floor M.; Menezes, Gisela L.G.; van den Bosch, Maurice A.A.J.; Gilhuijs, Kenneth G.A.; Peters, Nicky H.G.M.; Rubio, Isabel T.; Dixon, J. Michael
<x xml:space="preserve">Abstract</x> MRI is increasingly used in breast cancer patients. MRI has a high sensitivity compared to mammography and ultrasound. The specificity is moderate leading to an increased risk of false positive findings. Currently, a beneficial effect of breast MRI has been established in some patient groups and is debated in the general breast cancer population. The diagnostic ability of MRI and its role in various groups of breast cancer patients are discussed in this review. J. Surg. Oncol. 2014 110:26–31. © 2014 Wiley Periodicals, Inc.